Pengakuan Pendapatan dan Pengakuan Beban dalam Perspektif Akuntansi Syariah - Agus Setiawan; Akbar Aprian H; Gading Rayhan Al-Ikbar; Masyhuri Masyhuri (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
This study examines the recognition of revenue and expense from the perspective of Islamic accounting, emphasizing the integration between technical accounting standards, contractual substance, and ethical values derived from Sharia principles. Revenue recognition in Islamic accounting is not merely concerned with economic inflows but also with the legitimacy of transactions, clarity of contracts, and the realization of lawful benefits. Similarly, expense recognition reflects accountability in the use of resources and must correspond fairly to the benefits generated. The study adopts a qualitative literature-based approach by analyzing books, academic journals, and relevant accounting standards related to Islamic financial reporting. The discussion reveals that improper or unbalanced recognition of revenue and expense may distort financial performance and undermine stakeholder trust. Islamic accounting promotes prudence, fairness, and transparency to ensure that reported profits reflect actual economic conditions. The integration of revenue and expense recognition is therefore essential in producing reliable, ethical, and Sharia-compliant financial statements. This study highlights that Islamic accounting is not solely profit-oriented but is deeply rooted in moral responsibility and social accountability.